Impilikasi Kapitalisme Ekonomi Pada Petani Melayu Perkebunan Kopi Rakyat di Sumatera Selatan: Impilikasi Kapitalisme Ekonomi Pada Petani Melayu Perkebunan Kopi Rakyat di Sumatera Selatan - Raden Ayu Ritawati (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2019)
Modern economic capitalism has long engulfed smallholders in rural coffee plantations in South Sumatra. Intangibly, capitalism is always neatly wrapped up in goodness with many interests. The meaning of goodness here, how doers of economic capitalism with the spirit of morality have succeeded in deceiving coffee plantations farmers to become melted and obedient. This research is to find out the impact experienced by coffee plantation farmers who consciously form conflicts of interest and power. And the extent of the government's role in saving coffee farmers from the snares of dependency and hegemony of poverty. The field study was conducted in response to the behaviors and habits of the informants and the local culture that was observed on an ongoing basis. Then analyzed with descriptive qualitative methods based on the semantic relationship between variables. The results of the study prove that poverty that occurs in coffee farmers due to various factors, such as; historical elements as a result of colonial-feudalism, financial-industrial and technological-industrial dependency that made poor farmers helpless. Farmer expenditure, which was originally subsistence life, is increasingly in the form of money. No wonder consumerism is rampant and has become a new culture in rural communities. Increased habit of indebted to coffee bean collectors because of increasing population and economic pressure due to the inability of coffee farmers to adapt to the buying and selling economy. Where debt payments are made in installments when there is a coffee harvest with a longer payment term. Finally, the transformation of interests has succeeded in initiating the idea of ??mastering the economy of coffee farmers on moral and ethical ties for the values ??of the welfare of farmers who are hereditary and empowered for generations.